The role of TRPV4 in the regulation of retinal ganglion cells apoptosis in rat and mouse - Yi Wang; Wei Zhang; Guozheng Xu; Changwei Shi; Xiang Wang; Jianfeng Qu; Hongmei Wang; Chunhua Liu (Heliyon, 2023)
Retinal ganglion cell (RGC) damages are common in glaucoma, causing atrophy of the optic papilla, visual field damage, and visual loss. Transient receptor potential vanilloid 4 (TRPV4) is significantly expressed in the eyeball and is sensitive to mechanical and osmotic pressure. However, the specific role and mechanism of TRPV4 in glaucoma and RGC progression remain unclear. TRPV4 expression was detected in RGCs under different pressure culture conditions. We also explored the pressure effect on TRPV4 expression and the role and mechanism behind the functional regulation of RGCs. Immunofluorescence staining, western blotting, and TUNEL were utilized in this study. Our results established that TRPV4 was expressed in RGCs. TRPV4 expression was decreased at 40 mmHg and 60 mmHg, and the expression of BAX at 40 mmHg, 60 mmHg. Additionally, the expression of caspase 9 protein increased at 40 mmHg with the pressure increase compared with the conventional culture group. TUNEL staining revealed that the apoptosis rate of RGCs was elevated at 40 mmHg and 60 mmHg, compared with the traditional culture group. Therefore, the expression of BAX and caspase 9 increased, along with the apoptosis rate of RGCs compared with the control group. However, after TRPV4 antagonist treatment, the expression of BAX and caspase 9 decreased, and the apoptosis rate of RGCs decreased. Thus, TRPV4 may affect the mitochondrial apoptosis pathway, such as BAX and caspase 9, leading to the apoptosis of RGCs. The antagonists of TRPV4 could provide a new idea for clinically treating acute glaucoma.